Compilation of Henry's law constants (version 5.0.0) for water as solvent - Sander, Rolf (Atmospheric chemistry and physics, 2023)
Many atmospheric chemicals occur in the gas phase as well as in liquid cloud droplets and aerosol particles. Therefore, it is necessary to understand their distribution between the phases. According to Henry’s law, the equilibrium ratio between the abundances in the gas phase and in the aqueous phase is constant for a dilute solution. Henry’s law constants of trace gases of potential importance in environmental chemistry have been collected and converted into a uniform format. The compilation contains 46 434 values of Henry’s law constants for 10 173 species, collected from 995 references. It is also available on the internet at https://www.henrys-law.org (last access: October 2023). This article is a living review that supersedes the now obsolete publication by Sander (2015).